Apolipoprotein E Antibodies Affect the Retention of Passive Avoidance Memory in the Chick - Chris Lancashire; Radmila Mileusnic; Steven P.R. Rose (Neural Plasticity)
Isoforms of apolipoprotein E (ApoE) have been implicated as risk factors in Alzheimer’s disease. We have, therefore, examined the possible role of ApoE in memory formation, using a one-trial passive avoidance task in day-old chicks. Birds were trained on the task and then at various times pre or post-training were injected intracerebrally with anti-ApoE. Immunofluorescence staining demonstrated the presence of the antibody bound to the neuropil, close to the injection site and adjacent to the ventricle, with a residence time in the brain of up to 30 min. Chicks that were injected 30 min pre-training or just post-training with 5μg/ hemisphere of the antibody learned the task, but were amnesic when tested at 30 min or at subsequent times up to 24 hr Post-training. When tested at 24 hr, birds injected 5.5 hr post-training showed unimpaired retention. Birds injected with 5μg/hemisphere of anti-ApoA-I (which has a brain distribution similar to that of anti-ApoE) at 30 min pretraining showed no amnesia, indicating the specificity of the effect to the ApoE. Possible mechanisms for this effect are discussed.